Decomposition of eucalypt litter on rehabilitated bauxite mines - Ward, S.; Majer, Jonathan; O'Connell, A. (1991)
The initiation of nutrient cycling is important in developing a self-sustaining ecosystem, where inputs of fertilizer are not required, on rehabilitated open-cut mines. The loss of dry weight, surface area and nutrients from senescent jarrah (Eucalyptus marginata) leaves enclosed in litterbags for 18 months were measured on 27 rehabilitated bauxite mines and in two jarrah forests on the Darling Plateau in Western Australia. Respiration and acetylene reduction by the litter were also determined. Linear trends were found between litter decomposition on rehabilitated mines and understorey cover density, litter cover and a measure of the effect of the revegetation on soil moisture. During decomposition, N was retained relative to litter dry weight and, in most cases, amounts of N increased. Losses of Ca and S were correlated with dry weight losses. Sodium, Cl, Mg and K were lost from the litter by leaching. Rehabilitation techniques, including sowing a legume understorey and replacement of the topsoil, should favour the development of nutrient cycling on mined areas.